Péricles de Atenas e os dissoi logoi: entre Protágoras e Anaxágoras - Provetti Junior, José (2024)
The main problem established here is to verify if there were theoretical influences of Damon of Athens, Anaxagoras of Clazomena and Protagoras of Abdera in the decision-making of Pericles of Athens between the years 432-29 BC. as for the internal politics of Athens, its empire, the Persians and with the other Hellenics, especially the Peloponnesians; even if the possible influences have started before the time frame foreseen, the objective here is to verify if there were, what those influences were. From this possible theoretical identification, some of them already explained in the sources analyzed here, the working hypothesis is that there are others not formally registered that are likely to be identified and analyzed through the decision-making raised with the collegiate of strategoi that became proposals for analysis and possible approval by the Ekklesia. Studying the adaptation made by Pericles, his hetaireia regarding what was presented to the Ekklesia and finding out what was approved and implemented is one of the objectives set out here. Trying to understand how Pericles treated such measures during the management of the crisis resulting from the outbreak of the Second Peloponnesian War and the Pest that ravaged Athens until his death in 429 BC. With this investigation, an objective perception of the relationship and room for maneuver possible to Pericles will be achieved, through the approach that aims to lay bare the individual-society particularities in Athens at the beginning of the Second Peloponnesian War.